Consumer acceptance measurement focusing on a specified sensory attribute of products: Can the attribute-specified degree of satisfaction-difference (DOSD) method replace hedonic scaling?. (July 2019) - Kim, Min-A; van Hout, Danielle; Zandstra, Elizabeth H.; Lee, Hye-Seong
Highlight: The degree of satisfaction-difference (DOSD) method was further studied. The focus was on optimizing a specific consumer relevant attribute. The new DOSD method provided reliable product discrimination as hedonic scaling. The DOSD allowed to segment consumers based on the satisfaction to the reference. Results showed the potential of the DOSD as an alternative to hedonic scaling. Abstract: A specific attribute can play an important role in determining consumers' perceived quality and acceptance of a product. Kim, van Hout, Dessirier, and Lee (2018) proposed a new affective method, the degree of satisfaction-difference (DOSD) method, to study consumer acceptance in terms of overall satisfaction with products. In the present study, this DOSD method was further developed to assess satisfaction for a specified attribute of products rather than overall satisfaction, and this modification is referred to as the attribute-specified DOSD method. To test its applicability, 11 bouillon products (including a reference product) varying in viscosity were used as stimuli. Satisfaction with the perceived mouthfeel thickness, which is a viscosity-related sensory attribute, was evaluated with the attribute-specified DOSD method and with a 10-point category scale for overall liking as the control method. Two groups of consumers performed either the attribute-specified DOSD method or hedonic scaling over two repeated sessions. Results showed that the satisfaction patterns of the attribute-specified DOSD method were similar to those of the hedonic scaling across products, confirming that the mouthfeel thickness was a determinant of consumer acceptance for bouillon products. Examining the test reliability in terms of consistency of consumers' responses for the same stimulus in different sessions, both groups showed consistent results. The subjects who performed the attribute-specified DOSD method were also segmented based on the degree of satisfaction with the reference product. Here, each consumer sensory segment showed different patterns on satisfaction with other test products. These findings demonstrate the potential of the attribute-specified DOSD method for measuring the consumer responses to the level/quality of an important attribute/dimension and highlight its usefulness for consumer sensory segmentation.